Effects of carrageenan and glycerol on the starch retrogradation of moron (chocolate-milk sticky rice cake) - Naputo, Kimberly M.
Moron is a traditional glutinous rice cake from Leyte, Philippines, commonly sold in bundles and wrapped in banana leaves. Despite its popularity, it undergoes rapid quality degradation due to starch retrogradation, leading to moisture loss and textural hardening. This study simulated more recent handling conditions by storing the moron lots under refrigeration and examined the effects of κ-carrageenan (CGN) and glycerol (GLY) on texture and physicochemical stability. Phase I assessed the impact of CGN and GLY on texture after 12 days of storage. Both additives significantly affected all measured Texture Profile Analysis (TPA) parameters, with most treatments showing increased hardness, stiffness, and chewiness relative to the control. While GLY and CGN showed synergistic effects in enhancing springiness and adhesiveness, the increase in firmness may negatively impact sensory perception, underscoring the need for future sensory evaluation. In Phase II, CGN and GLY had limited influence on pH and water activity, though moisture content was significantly affected by GLY and its interaction with CGN by Day 12. GLY significantly (p<0.05) reduced syneresis, while CGN had no significant effect (p>0.05). The treatment with 0.5% CGN and 2% GLY yielded the lowest fluid release. Strong negative correlations were found between syneresis and texture parameters such as hardness and chewiness. In conclusion, GLY showed greater potential than CGN in reducing syneresis and enhancing moisture retention in moron.